A chitosan-thiomer polymer for highly efficacious adsorption of mercury. (1st March 2019) - Bhatt, Rahul; P, Padmaj
Graphical abstract: Highlights: A novel chitosan thiomer was fabricated and characterized. Exhibits very high adsorption capacity for Hg°, Hg 2+ and CH3 Hg + . Hg°, Hg 2+ and CH3 Hg + elution with 0.01 N thiourea, 0.01 N HClO4 and 0.2 N NaCl respectively. Abstract: Thiomers have recently attracted attention as effective adsorbents for Hg 2+ . In the present study a chitosan- thiobarbituric acid based thiomer(CTG) was investigated as a potential adsorbent for elemental mercury (Hg°), inorganic mercury (Hg 2+ ) and methyl mercury (CH3 Hg + ). CTG was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA). Adsorption experiments were performed to optimize the parameters for maximum removal of Hg°, Hg 2+ and CH3 Hg + . The experimental data fitted well to Freundlich isotherm and pseudo second order kinetic models with high R 2 and minimal error function values. The maximum adsorption capacities were determined to be 1367 ± 96.9, 2493 ± 174.6 and 2531 ± 178.4 mg/g for Hg°, Hg 2+ and CH3 Hg + respectively. Quantitative desorption of Hg°, Hg 2+ and CH3 Hg + from CTG could be performed using 0.01 N thiourea, 0.01 N HClO4 and 0.2 N NaCl respectively.